2014
DOI: 10.1016/s1473-3099(14)70920-x
|View full text |Cite|
|
Sign up to set email alerts
|

Ribavirin and interferon alfa-2a for severe Middle East respiratory syndrome coronavirus infection: a retrospective cohort study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
511
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 471 publications
(524 citation statements)
references
References 22 publications
3
511
0
10
Order By: Relevance
“…A recently published study that used the same regimen reported favorable 14-d survival. 22 Due to the limited number of subjects and lack of a control group in our study, we cannot make a conclusion about the use of this combination for Middle East Respiratory Syndrome coro- PRVC ϭ pressure-regulated volume control PIP ϭ peak inspiratory pressure CMV ϭ continuous mandatory ventilation navirus infection. Whether interferon ␤ could be a better replacement for peginterferon 2␣ also remains to be seen.…”
Section: Discussionmentioning
confidence: 90%
“…A recently published study that used the same regimen reported favorable 14-d survival. 22 Due to the limited number of subjects and lack of a control group in our study, we cannot make a conclusion about the use of this combination for Middle East Respiratory Syndrome coro- PRVC ϭ pressure-regulated volume control PIP ϭ peak inspiratory pressure CMV ϭ continuous mandatory ventilation navirus infection. Whether interferon ␤ could be a better replacement for peginterferon 2␣ also remains to be seen.…”
Section: Discussionmentioning
confidence: 90%
“…All PCR procedures were done at the KCDC. Antiviral treatment: Treatment was modified from previously published protocols (6,7). Pegylated interferon a-2a (Pegasys; Roche, Basel, Switzerland) was administered via subcutaneous injection at a dose of 180 mg/week for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Pegylated interferon a-2a (Pegasys; Roche, Basel, Switzerland) was administered via subcutaneous injection at a dose of 180 mg/week for 2 weeks. The dose of oral ribavirin (Copegus; Roche) was adjusted in accordance with calculated creatinine clearance and continued for 8-10 days (6,7). Patients with a creatinine clearance >0.833 mL/sec/m 2 received a 2,000 mg loading dose, followed by 1,200 mg every 8 h for 4 days, then by 600 mg every 8 h for 4-6 days.…”
Section: Methodsmentioning
confidence: 99%
“…The median time from admission to therapy with these two agents was 19 days, and thus any benefit effect might have not been evident [76]. A larger number of 20 patients received ribavirin and interferon treatment at a median of 3 days [77]. The therapy resulted in improved 14-day survival of 70% (14 of 20 patients) in the treatment group, compared to 29% (7 of 24 of patients) in the comparison group (p = 0Á004) with no survival advantage at 28 days (30 vs 17%, p = 0Á54) [77].…”
Section: Currently Available Antiviral Agents and Vaccinesmentioning
confidence: 99%
“…A larger number of 20 patients received ribavirin and interferon treatment at a median of 3 days [77]. The therapy resulted in improved 14-day survival of 70% (14 of 20 patients) in the treatment group, compared to 29% (7 of 24 of patients) in the comparison group (p = 0Á004) with no survival advantage at 28 days (30 vs 17%, p = 0Á54) [77]. In an experimental model of MERS-CoV infection in mice, a recombinant receptor-binding domain (rRBD) of MERSCoV spike (S) glycoprotein in association with Fc of human IgG (RBD-Fc) induced neutralizing antibodies [78,79].…”
Section: Currently Available Antiviral Agents and Vaccinesmentioning
confidence: 99%